Identification of a New High Essential Oil Yielding Variety "Jor Lab AC-1"of Acorus calamus L. Issue 3 (4th May 2019) - Lal, Mohan; Borah, Angana; Pandey, Sudin Kumar
Abstract: Acorus calamus L. (sweet flag) is an aromatic medicinal plant, generally found in the temperate and subtropical regions of the world. It is used since ages in traditional medicine and now-a-days it is also used in various commercial and pharmaceutical industries for its medicinal and aromatic properties. The aim of the present study was to identify a high essential oil yielding variety of A. calamus . In this study, fourty germplasm were collected from different parts of India and planted in RBD during the year 2014. All agronomical and oil quality data were recorded. After evaluation of two season data, a high essential oil genotype was identified and was named as "Jor Lab AC-01". The elite genotype was evaluated in five different locations (Jorhat, Lakhimijan, Pasighat, Imphal and Madang) during the year 2017. Data recorded from the five locations across Northeast India gave satisfactory and stable results. The average essential oil yield was found to be 1.20 %, which is significantly higher as compared to the check variety (0.62 %). The line is suitable for further commercial cultivation. This new variety can be commercialized, and the farmers would be benefited by this superior variety.